Integrated Development of Nangarhar Province, Afghanistan - Planning Commission (Planning Commission, 2006)
The Integrated Development Project in Nangarhar Province, Afghanistan, initiated by the Government of India, aims to promote sustainable economic growth and social development in a region challenged by low agricultural productivity and high poppy cultivation. Key interventions include modernizing agriculture through high-yield seeds, establishing a Farm Science Centre, enhancing livestock and dairy production, and promoting food processing and traditional crafts. Infrastructure improvements, such as irrigation management, road construction, and power generation, are prioritized to facilitate trade and agricultural efficiency. Human capital development through education and health services forms a central component of the initiative. With an estimated financial commitment of $1.64 million, the project seeks to serve as a model for sustainable development in Afghanistan, fostering economic recovery, stability, and international collaboration.
Report of the Visiting Team of Experts
Report of the Visiting Team of Experts
Keywords: Nangarhar Province; Integrated Development; Agriculture; High-Yield Seeds; Dairy Production; Food Processing; Infrastructure; Irrigation; Road Development; Education; Health Services; India-Afghanistan Cooperation